MODIFYING FUZZY PUPPET AS EPUGA (ENGLISH PUPPET GAME) FOR TEACHING SPEAKING - Nailul Fauziyah; Desyana Rizqi Alviani (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
The use of media in teaching speaking is important. Lack of teaching media may make the students face some difficulties such as uttering their idea, referring their minds, and getting the confidence to speak. Thus, creating new media, methods, strategies, or approaches will influence the students to enjoy the learning process. This current research was conducted to design a teaching medium for speaking skills in narrative texts. By implementing three phases in the designing process of the medium, the EPUGA (English Puppet Game) was created. Based on the result of interviewing the teacher, the needs could be identified to design and develop the first prototype of EPUGA. After its prototype was created, then, it was validated by the expert. Generally, the expert suggested to make larger the size and the fonts of the card and adding the instruction on its usage. The final stage was done through an assessment conducted by the teacher’s observation and students’ responses. Accordingly, the students enjoyed and were active in practicing their speaking ability through playing the EPUGA. Thus, the EPUGA reflected that it was an attractive and interesting medium of English teaching-learning; it included the appropriate medium to encourage students in speaking; and its materials, rules, and procedures were easy to understand.